Tobacco smoking - Healey, Justin (Issues in society (Balmain, N.S.W.), 2011)
Tobacco smoking kills up to half of its users and has a global annual death toll of more than five million people. It is the largest cause of preventable death in the western world. Around 3 million Australians are daily smokers, many of whom are socially disadvantaged. This title reveals the toxic contents of tobacco and the health effects of smoking (including passive smoking) on the body. The book also addresses a number of commonly held myths and misconceptions about the risks and impacts of smoking. A range of different quitting methods and products for overcoming nicotine addiction is al.